Pendayagunaan Sumber Daya Filantropi Perspektif Hadis: : Studi Peran Baznas Kota Gorontalo - Muhammad Nasir (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This research investigates how the hadith guidelines on the use of zakat, infaq, and shadaqah are used to impose zakat and shadaqah and devise ways to use the philanthropic resources of Muslims, particularly in the municipality of Gorontalo. The approach used was a legal and social content analysis. The research result showed that the Gorontalo City Baznas Program is a positive economic empowerment program called Kota Gorontalo Makmur, referring to the prophet's hadith. This initiative was in the form of business capital assistance to the poor to conduct profitable enterprises, such as farming, fishing, planting, livestock rearing, sale, household crafts, etc. Every year, Gorontalo City Baznas distributes this program to 50 citizens like the sold products. This program has been applied since July 2017. For the first phase, 23 people have received capital assistance amounting to Rp. 5,000,000/person with two disbursements. The initial stage was worth Rp. 3,000,000 and later in the second stage the remaining Rp. 2,000,000 was given to mustahiq.